Selective herbicide safening in dicot plants: a case study in Arabidopsis - Pingarron-Cardenas, Gabriela; Onkokesung, Nawaporn; Goldberg-Cavalleri, Alina; Lange, Gudrun; Dittgen, Jan; Edwards, Robert (Frontiers in Plant Science, 2024)
Safeners are agrochemicals co-applied with herbicides that facilitate selective control of weeds by protecting monocot crops from chemical injury through enhancing the expression of detoxifying enzymes such as glutathione transferases (GSTs). Even though the application of safeners causes the induction of genes encoding GSTs in model dicots such as Arabidopsis thaliana, safeners do not protect broadleaf crops from herbicide injury. In this study, we proposed that the localized induction of Arabidopsis GSTs and the fundamental differences in their detoxifying activity between dicot and monocot species, underpin the failure of safeners to protect Arabidopsis from herbicide toxicity. Using the herbicide safener, isoxadifen-ethyl, we showed that three tau (U) family GSTs namely AtGSTU7, AtGSTU19 and AtGSTU24 were induced with different magnitude by isoxadifen treatment in root and rosette tissues. The higher magnitude of inducibility of these AtGSTUs in the root tissues coincided with the enhanced metabolism of flufenacet, a herbicide that is active in root tissue, protecting Arabidopsis plants from chemical injury. Assay of the recombinant enzyme activities and the significant reduction in flufenacet metabolism determined in the T-DNA insertion mutant of AtGSTU7 (gstu7) in Arabidopsis plants identified an important function for AtGSTU7 protein in flufenacet detoxification. In-silico structural modeling of AtGSTU7, suggested the unique high activity of this enzyme toward flufenacet was due to a less constrained active site compared to AtGSTU19 and AtGSTU24. We demonstrate here that it is possible to induce herbicide detoxification in dicotyledonous plants by safener treatment, albeit with this activity being restricted to very specific combinations of herbicide chemistry, and the localized induction of enzymes with specific detoxifying activities.